PENGARUH PERENCANAAN PAJAK, BEBAN PAJAK TANGGUHAN DAN TARIF PAJAK TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nafiah, Zumrotun; Hendrayanti, Silvia; Sopi, Sopi; Chasanah, Nur (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
The evaluation of a company can be measured by how much profit the company makes. Inmanagements intention and desire to reduce and achieve tax minimization, management will tend to work towards tax reduction. This study aims to examine the effect of Tax Planning, Deferred Tax Expenses and Tax Rates on Earnings Management. The population in this study are manufacturing companies in the Consumer Goods Industry Sector listed on the Indonesia Stock Exchange (IDX). Based on the purposive sampling method, the number of samples in this study were 32 companies. The analysis used in this study is descriptive statistical test, classical assumption test (normality test, heteroscedasticity test, multicollinearity test, and autocorrelation test), multiple linear regression test analysis, and hypothesis testing (coefficient of determination test and t test). The measuring tool used for this analysis is the SPSS Version 26 program. That based on the partial test (t test), Tax Planning has a negative and insignificant effect on Earnings Management and Deferred Tax Expense has a positive and insignificant effect on Earnings Management, while Tax Rates have a positive and significant effect on Earnings Management. Together (f test), Tax Planning, Deferred Tax Expenses and Tax Rates have an effect on Earnings Management with a significance value of 0.003 <0.05. For further research, it is recommended to expand the number of samples, not only using one sector but using all sectors listed on the Indonesia Stock Exchange.